Sediment variability in intermittently extracted sandbanks in the Belgian part of the North Sea - Kint, Lars; Barette, Florian; Degrendele, Koen; Roche, Marc; Van Lancker, Vera (Frontiers in Earth Science, 2023)
In the Belgian part of the North Sea, sand for beach and foreshore nourishments is extracted from the Hinder Banks, about 40 km offshore. The extraction is not screened for shells and other very coarse material, as is the case for sand extraction for industrial use. Intermittent but intensive sand extraction took place from 2012 to 2019 on the Oosthinder, and since 2019 on the Noordhinder. To better understand sediment variability during human-induced disturbance of the seabed, both sandbanks have been monitored using multibeam bathymetry and backscatter, and Reineck box cores on board of the Research Vessel Belgica A962. Acoustic and sediment data were preferably jointly collected within a one-week period to substantiate the interrelationships. Very well-sorted medium sands with low backscatter values (-28 to -33 dB) are detected near the top of the sandbank, while (moderately) well-sorted coarser sands and shell fragments with high backscatter values (-20 to -24 dB) are detected in the deeper parts of the sandbank slope. This applies to both undisturbed areas, as well as recently and longer disturbed sand extraction areas. Although natural conditions such as sandwave movement and storms may mask early sediment changes, seven years of intermittent and intensive sand extraction on the upper parts of a gentle sandbank slope caused a seabed deepening of at least 2 m, a backscatter decrease between 5 and 8 dB, a reduction in carbonate content by 1 to 5 % and an increase in organic matter content by 1 to 2 %. Backscatter decrease and decrease in carbonate content were related, confirmed by an acoustic-sediment correlation analysis. A spreading of the more homogeneous, very well-sorted medium sands from the sandbank crest to the upper parts of the sandbank slope was observed. Two years after the cessation of the operations, the carbonate content increased and organic matter content decreased by 1 to 2 %. Possibly, these are signs of a slow return to the original sediment characteristics.